Religion And Tourism Growth In Aceh: A Conceptual Framework - Mohamad Handi Khalifah; Iqlima Azhar; Muhammad Salman; Mayang Murni (Jurnal Penelitian Ekonomi Akuntansi, 2023)
This research aims to discover and assess the halal tourism potential in Aceh Province. This research is qualitative and uses the literature review method. The findings of this study indicate that Aceh has excellent potential as a halal tourist destination, with natural wealth comparable to other well-known tourist destinations in Indonesia; however, Aceh Province, as the only province in Indonesia that follows Islamic Sharia law, must identify market segments in order to promote things that will appeal to foreign tourists. Aceh has met all of these criteria as a norm for halal tourism zones, according to the Global Travel Market Index (GMTI).